HUBUNGAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR PADA PELATIHAN PUBLIC SPEAKING BAGI SDM KESEHATAN DI BBPK CILOTO - Sausan Tasyandra Yasaroh, - (2022)
This study examines the relationship between learning motivation and learning outcomes in public speaking training at BBPK Ciloto. The purpose of this study is to determine the relationship between learning motivation and learning outcomes in public speaking training at BBPK Ciloto and how big the relationship between learning motivation and learning outcomes in public speaking training at BBPK Ciloto. This research is supported by theoretical conceptual ideas regarding: Concepts of Community Education, Training, Motivation, Learning Motivation, and Learning Outcomes. The hypothesis of this study is that there is a relationship between learning motivation and learning outcomes in public speaking training for Health Human Resources at BBPK Ciloto. This study uses a descriptive method with a quantitative approach. Data collection techniques in this study are documentation, observation and questionnaire studies. The population of this study was 60 while the sample in this study amounted to 52 people. Hypothesis testing in this study used the Pearson product moment test. The results of the Pearson Moment Product Correlation in this study have a correlation coefficient (r) of 0.457 with a significance value of 0.001. It can be concluded that the correlation coefficient of 0.457 is low because it is in the range (0.400 - 0.599) and there is also a positive and significant influence on learning motivation on the learning outcomes of participants in public speaking training for Health HR which is aimed at ttcount of 3.735 which is greater than ttable. so tcount > ttable (3.735 > 1.675). While the magnitude of the relationship between learning motivation and learning outcomes in this study was 20.8%, while the other 79.8% were related by other factors not included in this study.